SELF REPORTED TOOTH DISCOLORATIONS AMONG PATIENTS SEEN AT DENTAL CENTER UNIVERSITY COLLEGE HOSPITAL IBADAN - Gbadebo, Shakeerah O (J West Afr Coll Surg, 2015)
BACKGROUND: Tooth discoloration is an aesthetic problem that is linked to a variety of causes and it could be a source of embarrassment, leading to reduced self-esteem. AIM: To determine the prevalence of self reported tooth discoloration and the distribution of the different intrinsic tooth discolorations. METHODOLOGY: A retrospective study that reviewed the distribution of tooth discoloration reported by patients that presented for treatment of tooth discoloration at conservation clinic of the dental centre University College Hospital, Ibadan between December 2011 and December 2014. Data collected from patients’ case files included patients’ demographics, type of tooth discoloration as diagnosed by attending consultant and treatment offered. Data were analyzed using SPSS version 20. Frequencies and means were used for continuous variables while chi square was used to compare the categorical variables. P value was set at ≤ 0.05. RESULTS: One hundred and thirty six patients reported tooth discoloration as their major reason for presentation at the clinic. The patients were between age 16-75 years with mean age of 35.62±14.31 years and male to female ratio of 1:1.13. Prevalence of reported tooth discolouration during the study period was 9.8%. Pulpal necrosis was the most reported cause of (86.8%) tooth discolouration, while fluorosis was the least (0.7%) reported. Non vital tooth bleaching was the most common treatment (72.1%) offered for tooth discoloration. No significant comparison was observed between gender and type of tooth discoloration, p=0.088. CONCLUSION: Pulpal necrosis is a major cause of discoloration which leads to reduced self esteem. There is need to improve on dental awareness on causes of tooth discoloration for prevention and early presentation for management.